Comparative Analysis of Employee Welfare According to the Labor Law VS Omnibus Law - Wardah, Siti Syarifah Wafiqah (Universitas Negeri Makassar, 2024)
The passing of the Job Creation Law or Omnibus Law is a new law that combines regulations and cuts several articles from previous laws, including articles on employment in the Labor Law, into simpler regulations inviting various parties who agree and disagree. This study aims to provide a comparative analysis between Law Number 13 of 2003 concerning Labor and Law Number 6 of 2023 concerning Job Creation in terms of employee welfare. The research method uses normative juridical with analytical descriptive research specifications, Primary materials collected include the 1945 Constitution, Law Number 13 of 2003, and Law Number 6 of 2023 on the employment cluster. Secondary materials consist of books, experts' opinions, the internet, e-journals, and other written works related to the research subject. Based on the results of the study, due to simplification by the Omnibus Law there are several articles that have been eliminated which were previously regulated by the Labor Law, this has led to a decrease in welfare for the Employees.